Actuating Guidance and Counseling Services in Schools with Imbalanced Counselor–Student Ratios: Insights from a Focus Group Discussion Study - Fajar Juliansyah; Uman Suherman; Ibrahim Alhakim (Journal of Education and Counseling (JECO), 2025)
This study analyzes the implementation of management functions, particularly the actuating aspect, in the delivery of guidance and counseling services in schools with an unbalanced counselor–student ratio. Using a qualitative case study approach, participants were selected purposively from seven Guidance and Counseling teachers at junior, senior, and vocational high schools in West Java who directly manage disproportionate student ratios. Data were collected through Focus Group Discussions (FGD), which were audio- and video-recorded and transcribed to ensure data accuracy and validity. The data were then analyzed using the Miles and Huberman interactive model, which involves data reduction, display, and conclusion drawing. The findings show a significant ratio gap (1:450–1:850) compared to the ideal 1:150 set by Permendikbud No. 111 of 2014, resulting in the dominance of responsive services and limited implementation of basic and individual planning services. Despite this, teachers adapted the actuating function through modified service methods, stakeholder collaboration, and the use of technology to improve efficiency. Partial effectiveness was found in responsive and career guidance services, contributing to improved student attendance and success. The study recommends strengthening policies by adding Guidance and Counseling teachers, allocating classical guidance hours, and developing a Guidance and Counseling Management Information System to enhance the effectiveness, efficiency, and accountability of management functions in supporting holistic student development.